Ta’dib Penanaman Adab di Pesantren - Sunar, Sunar; Al ‘Ithriy, Abu Husein Ibrahim; Pambudi, Riski Kristianto (TSAQOFAH, 2026)
The concept of ta’dib constitutes the core of Islamic education, focusing on the inculcation of adab, the formation of akhlak (moral character), and the gradual introduction of truth to students. In the pesantren tradition, ta’dib serves as the principal foundation that distinguishes the pesantren educational system from other institutions, as it emphasizes not only the transfer of knowledge but also the formation of students’ character and personality as santri. This study aimed to examine in depth the concept of ta’dib in Islamic education by highlighting its implementation in the context of pesantren. The method employed was a literature study that reviewed various relevant sources, including books, journal articles, and previous research. The findings show that the inculcation of adab is carried out through various methods, including dialogue (hiwar), exemplary modeling (uswah), habituation (riyadhah), inspirational stories (ibrah), advice (mau’idzah), motivation and warning (targhib wa tarhib), and the use of parables (amtsal). Earlier scholars emphasized that adab is superior to knowledge because adab protects human beings from wrongdoing and makes their knowledge more beneficial. These findings affirm that, amid contemporary moral and social challenges, the strengthening of ta’dib is essential for shaping a morally upright generation not only in pesantren but also in schools and family environments, thereby enabling Islamic education to contribute significantly to the character formation of the Muslim community.